2023
DOI: 10.7759/cureus.35967
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Attention Deficit Hyperactivity Disorder Among Children in Makkah Region, Saudi Arabia

Abstract: Introduction Attention-deficit/hyperactivity disorder (ADHD) is the most common behavioral disorder in children and is described as a disease involving loss of self-control. The core symptoms of ADHD are inattentiveness, impulsivity, and motor unrest. Furthermore, poor concentration, distraction, hyperactivity, and poor academic achievement at school or at home are other symptoms. ADHD, like other prevalent medical disorders such as asthma and schizophrenia, may be impacted by several genes and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Specifically, seven studies within the dataset investigated ADHD prevalence across a wider age spectrum, ranging from 5 to 18 years. Interestingly, the reported prevalence for these studies was extremely high, ranging between 32% and 40% 35 45 57 58 60 62 71 82. Furthermore, we observed that studies using different versions of the DSM show varying prevalence rates.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Specifically, seven studies within the dataset investigated ADHD prevalence across a wider age spectrum, ranging from 5 to 18 years. Interestingly, the reported prevalence for these studies was extremely high, ranging between 32% and 40% 35 45 57 58 60 62 71 82. Furthermore, we observed that studies using different versions of the DSM show varying prevalence rates.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, 63 articles involving 849 902 participants were included in the meta-analysis (as shown in PRISMA, figure 1). 35–97 The studies and participant characteristics are reported in online supplemental table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2023, Alotaibi et al 5 used Long Time Average Spectrograms (LTAS) to examine recordings made before and after effective speech treatment for children with functional dysphonia. The study included 174 participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attention-De cit Hyperactivity Disorder (ADHD) is a neuropsychiatric disorder that affects between 7.2-15% of children worldwide [1]. Recently, with the advent of the Internet of Things and arti cial intelligence, there have been reported innovations not only for improving cognitive, behavioral, and social aspects of children with ADHD [2], but also for monitoring and diagnosis with smart algorithms [3].…”
Section: Introductionmentioning
confidence: 99%